Motives for using reels TikTok social media among Children - Kholili, Prasetyo Eryan; Wijiharto Tunggali , Ade Putranto Prasetyo (COMMICAST, 2023)
Technology that develops from time to time makes a person more active in using social media. Cellular phone companies also develop various services (4G, 5G and others) to support these needs. Social media has become an integral part of everyday life among children, where they can share information or do other things for fun. This is a necessity for them. Reels TikTok is one type of social media that is currently widely used by children. Researchers want to see the pattern of using Tiktok among teenagers. This study uses a qualitative descriptive method, with five active teenagers who use Tiktok as samples or informants. Data collection techniques in this study were observation, interviews and collecting documents in the form of photos and other files. From the results of the study, it can be concluded that Tiktok is a social media that is able to meet one's needs, namely cognitive, affective, personal integration, social integration and imagining needs.